Synthesis and characterization of paramagnetic Mn doped Ca2P2O7 ceramics by sol-gel method - Kaygili, Omer (Korean Assoc Crystal Growth, Inc, 2015)
Pure calcium pyrophosphate (Ca2P2O7) and Mn doped Ca2P2O7 based ceramics were synthesized by sol-gel method, and were characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR), vibrating sample magnetometer (VSM), scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. The average crystallite size and crystallinity are affected by the addition of lower amount Mn, whereas, the content of Mn having higher amounts did not cause a remarkable effect on these parameters. The bands belonging to the pyrophosphates were detected. The ceramics exhibit the paramagnetic behavior at room temperature and the magnetic susceptibility increases from 7.28 x 10(-7) to 2.48 x 10(-5) emu g(-1) Oe(-1) with the addition of Mn. The microstructure of the ceramics is affected by the content of Mn. All the samples are composed of the fine-grained particles, and no impurity is observed.
Keywords: Magnetic property; Sol-gel method; Ca2P2O7 ceramic